Exploring Teacher Leadership in Public Schools in Baku - Bayandurova, Khayala; Khalilli, Fidan; Lutvalizada, Aytan (ADA University, 2023)
Teacher leadership is vital to every school community. Teachers shape the standards of practice, the nature of communication, and the sense of values that define a school culture. The majority of the population attends public schools for basic education; however, there are several private schools that one can select from and attend as well. This research study investigates how school administrators and teachers define teacher leadership as well as how principles support teacher leadership in Baku public schools. Interviews were used by the researchers as the main source of data collection to determine principals and teachers' definition of teacher leadership and principals' support for teacher leaders. The findings of the study demonstrate that a minority of teachers cannot describe teacher leadership and teachers and school administrators have separate views on this concept. Based on our findings, principals completely support teacher leaders in both formal and informal teacher leadership responsibilities. Support for teachers and administrators in raising awareness on teacher leadership with the help of trainings, workshops, or instructional blogs on teacher leadership may be quite beneficial.
Keywords: Teacher leadership -- Azerbaijan; School principals -- Leadership; Educational leadership -- Professional development; Education